INVESTIGATION OF ANTIBACTERIAL ACTIVITY OF OINTMENTS WITH LEVOFLOXACIN AND DECAMETOXINE ON CLINICAL STRAINS - AGENTS OF WOUND INFECTIONS - Штанюк, Є.А. (World of Medicine and Biology, 2015)
The actual problem is medical treatment of surgical wounds complicated by multiresistant strains of bacteria to antibiotics. Resistance of bacterial microflora to antimicrobial agents is increasing every year and requires implementation in medical practice of new effective drugs. According to the literature the main causative agents of inflammatory diseases is Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. It is advisable to monitor the efficiency of modern antibiotics (for example fluoroquinolones), antiseptics and other excipients that can potentially overcome bacterial resistance to these antibiotics. The purpose of the study. Research by agar diffusion of antibiotic action of ointments levofloxacin 0.1% and ointment decametoxine on standard and clinical strains of S. aureus, E. coli and P. aeruginosa and the search for solutions to overcome the resistance of clinical strains these types of bacteria to levofloxacin. Materials and methods. In the experiment, 10 samples of ointments with levofloxacin 0.1% and / or 0.5% decametoxine were used for water-soluble base, consisting of poloxamer, polyethylenes and propyleneglycol. Furthermore, some additional samples of ointments were containing 0.5% disodium EDTA complexing (DNE), 10% penetration amplifier of dimethylsulfoxide (DMSO) or N-metylpyrolidon (NMP) or transkutol (monoetylovyy ether of diethylene glycol – MED), 0.5% cationic surfactant active substances (SAS) or miramistin etoniy, or 1% anionic surfactant sodium lauryl sulfate (SLS). Antibiotic ointments action tested on standard and nosocomial multiresistant strains of S. aureus, E. coli and P. aeruginosa. Each study was repeated 6 times. Reliability of the results was determined by Student’s t test (p